Generating normative data from web-based administration of the Cambridge Neuropsychological Test Automated Battery using a Bayesian framework - Wragg, Elizabeth; Skirrow, Caroline; Dente, Pasquale; Cotter, Jack; Annas, Peter; Lowther, Milly; Backx, Rosa; Barnett, Jenny; Cree, Fiona; Kroll, Jasmin; Cormack, Francesca (Frontiers in Digital Health, 2024)
IntroductionNormative cognitive data can distinguish impairment from healthy cognitive function and pathological decline from normal ageing. Traditional methods for deriving normative data typically require extremely large samples of healthy participants, stratifying test variation by pre-specified age groups and key demographic features (age, sex, education). Linear regression approaches can provide normative data from more sparsely sampled datasets, but non-normal distributions of many cognitive test results may lead to violation of model assumptions, limiting generalisability.MethodThe current study proposes a novel Bayesian framework for normative data generation. Participants (n = 728; 368 male and 360 female, age 18–75 years), completed the Cambridge Neuropsychological Test Automated Battery via the research crowdsourcing website Prolific.ac. Participants completed tests of visuospatial recognition memory (Spatial Working Memory test), visual episodic memory (Paired Associate Learning test) and sustained attention (Rapid Visual Information Processing test). Test outcomes were modelled as a function of age using Bayesian Generalised Linear Models, which were able to derive posterior distributions of the authentic data, drawing from a wide family of distributions. Markov Chain Monte Carlo algorithms generated a large synthetic dataset from posterior distributions for each outcome measure, capturing normative distributions of cognition as a function of age, sex and education.ResultsComparison with stratified and linear regression methods showed converging results, with the Bayesian approach producing similar age, sex and education trends in the data, and similar categorisation of individual performance levels.ConclusionThis study documents a novel, reproducible and robust method for describing normative cognitive performance with ageing using a large dataset.